Elementos da cultura que dificultam a entrega de resultados em um órgão público da administração direta - Azevedo, Isnar Pittan (2015)
This work falls within the field of discussions related to the impact of national culture on organizational culture, offering, through a case study, specifics of a Brazilian national government agency. The work is dedicated to achieving a diagnosis of the functioning features of that agency, in order to understand how cultural elements interfere in its capacity to deliver results. Starting from a theoretical framework that characterizes the traits of national culture in the Brazilian management style, as well as from the so-called 'intangibles' in management, the organizational dynamics of the agency in point were scrutinized, with a view to identifying the intangible liabilities that make it difficult for it to deliver. Through the lens of its own servants, thanks to twenty-one in-depth interviews, cultural and management specificities of the agency were identified, giving occasion to the discussion of topics such as: mission, strategic planning, leadership, processes and information technology, personnel, training and allocation of resources. The results of the analysis have led to the vision of a pressing need for the organization to deal with the human factor with a strategic vision, therefore creating a new capacity-building environment aimed at organizational excellence. Alternatives to launch the paving of this new path have been proposed, a path that would have as its main pillars the integration of people and their involvement in the search for results.